The Evolution of Transjugular Intrahepatic Portosystemic Shunt: Tips. (18th March 2014) - Fanelli, Fabrizio
Abstract : Since Richter's description in the literature in 1989 of the first procedure on human patients, transjugular intrahepatic portosystemic shunt (TIPS) has been worldwide considered as a noninvasive technique to manage portal hypertension complications. TIPS succeeds in lowering the hepatic sinusoidal pressure and in increasing the circulatory flow, thus reducing sodium retention, ascites recurrence, and variceal bleeding. Required several revisions of the shunt TIPS can be performed in case of different conditions such as hepatorenal syndrome, hepatichydrothorax, portal vein thrombosis, and Budd-Chiari syndrome. Most of the previous studies on TIPS procedure were based on the use of bare stents and most patients chose TIPS 2-3 years after traditional treatment, thus making TIPS appear to be not superior to endoscopy in survival rates. Bare stents were associated with higher incidence of shunt failure and consequently patients required several revisions during the follow-up. With the introduction of a dedicated e-PTFE covered stent-graft, these problems were completely solved, No more reinterventions are required with a tremendous improvement of patient's quality of life. One of the main drawbacks of the use of e-PTFE covered stent-graft is higher incidence of hepatic encephalopathy. In those cases refractory to the conventional medical therapy, a shunt reduction must be performed.